Vitamin D and Male Sexual Function: A Transversal and Longitudinal Study - Giacomo Tirabassi; Maurizio Sudano; Gianmaria Salvio; Melissa Cutini; Giovanna Muscogiuri; Giovanni Corona; Giancarlo Balercia (International Journal of Endocrinology)
Background. The effects of vitamin D on sexual function are very unclear. Therefore, we aimed at evaluating the possible association between vitamin D and sexual function and at assessing the influence of vitamin D administration on sexual function. Methods. We retrospectively studied 114 men by evaluating clinical, biochemical, and sexual parameters. A subsample (n=41) was also studied longitudinally before and after vitamin D replacement therapy. Results. In the whole sample, after performing logistic regression models, higher levels of 25(OH) vitamin D were significantly associated with high values of total testosterone and of all the International Index of Erectile Function (IIEF) questionnaire parameters. On the other hand, higher levels of total testosterone were positively and significantly associated with high levels of erectile function and IIEF total score. After vitamin D replacement therapy, total and free testosterone increased and erectile function improved, whereas other sexual parameters did not change significantly. At logistic regression analysis, higher levels of vitamin D increase (Δ-) were significantly associated with high values of Δ-erectile function after adjustment for Δ-testosterone. Conclusions. Vitamin D is important for the wellness of male sexual function, and vitamin D administration improves sexual function.